Answer:
see explanation
Explanation:
Given the 3 equations
3x + 5y + 5z = 1 → (1)
x - 2y = 5 → (2)
2x + 4y = 11 → (3)
Use (2) and (3) to solve for x and y
Multiply (2) by 2
2x - 4y = 10 → (4)
Add (3) and (4) term by term
4x = 21 ( divide both sides by 4 )
x =
![(21)/(4\\)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/tqrayw52fs2wl2ipm2iobqi53bu9x2ivwn.png)
Substitute this value of x into (3)
2 ×
+ 4y = 11
+ 4y = 11 ( subtract
from both sides )
4y =
( divide both sides by 4 )
y =
![(1)/(8\\)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/fucgxq4imfgugv1j9jpxf4jz3uopub1tdm.png)
Substitute the values of x and y into (1) and solve for z
3 ×
+ 5 ×
+ 5z = 1
+
+ 5z = 1
+ 5z = 1 ( subtract
from both sides )
5z = -
( divide both sides by 5 )
z = -
![(123)/(40)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/1i9xvlhkmfwyzzvnfibtl1yp1egks9llk8.png)
Solution is
x =
, y =
, z = -
![(123)/(40)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/1i9xvlhkmfwyzzvnfibtl1yp1egks9llk8.png)